Development and Validation of a GC-FID Method for the Quantitation of 20 Different Acidic and Neutral Cannabinoids - Gul, Waseem; Ibrahim, Elsayed A.; Gul, Sharjeel W.; Shahzadi, Iram; Radwan, Mohamed M.; Chandra, Suman; Lata, Hemant; ElSohly, Mahmoud A. (Planta Medica, 2023)
For decades, Cannabis sativa had been illegal to sell or consume around the world, including in the United States. However, in light of the recent 2018 Farm Bill and the legalization of hemp across the US, various cannabis preparations have flooded the market, making it essential to be able to quantitate the levels of the different acidic and neutral cannabinoids in C. sativa and to have a complete cannabinoid profile of the different chemovars of the cannabis plant. A GC-FID method was developed and validated for the analysis of 20 acidic and neutral cannabinoids as trimethylsilyl (TMS) derivatives. The analyzed cannabinoids include cannabidivarinic acid (CBDVA), cannabidiolic acid (CBDA), cannabinolic acid (CBNA), cannabielsoic acid (CBEA), cannabicyclolic acid (CBLA), cannabichromenic acid (CBCA), trans-Δ9-tetrahydrocannabivarinic acid (Δ9-THCVA), trans-Δ9-tetrahydrocannabinolic acid A (Δ9-THCAA), cannabigerolic acid (CBGA), cannabidiol (CBD), cannabicyclol (CBL), cannabidivarin (CBDV), trans-Δ9-tetrahydrocannabivarin (THCV), cannabichromene (CBC), trans-Δ8-tetrahydrocannabinol (Δ8-THC), trans-Δ9-tetrahydrocannabinol (Δ9-THC), cannabigerol (CBG), cannabinol (CBN), cannabicitran (CBT), and cannabielsoin (CBE). The method limit of detection (LOD) was as low as 0.1 µg/mL, while the limit of quantitation ranged from 0.25 µg/mL to 0.5 µg/mL. The precision (%RSD) was < 10%, while trueness ranged from 90 – 107%. The developed method is simple, accurate, and sensitive for the quantitation of all 20 acidic and neutral cannabinoids. Finally, the proposed method was successfully applied to the quantitation of the cannabinoids in different cannabis chemovars grown at the University of Mississippi.
Keywords: Cannabis sativa; Cannabaceae; cannabinoids; GC-FID; derivatization